JOOTHAN: A VOICE FROM THE DALIT EXPERIENCE - Dalavai, V. R. (ShodhKosh: Journal of Visual and Performing Arts, 2021)
The article "Joothan: A Voice from the Dalit Experience" looks at the long-standing social disparities and caste-based discrimination in India, focusing on Omprakash Valmiki's autobiography Joothan. Valmiki's work is a moving portrayal of his life as a Dalit, highlighting the terrible reality of untouchability and the structural oppression that underprivileged populations experience. The article places Joothan within the larger context of Dalit literature, emphasizing its significance in post-independence India. Dr. Dalavai examines how Valmiki's tale breaks new ground by giving voice to realities that have previously been excluded from mainstream Hindi literature. The article also discusses the historical and social factors that support casteism in India, connecting parallels to worldwide issues such as racism and social injustice to achieve true equality and justice. Ultimately, it emphasizes the necessity for social reform.